2010
DOI: 10.1007/s11856-010-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Base sizes for sporadic simple groups

Abstract: Let G be a permutation group acting on a set Ω. A subset of Ω is a base for G if its pointwise stabilizer in G is trivial. We write b(G) for the minimal size of a base for G. We determine the precise value of b(G) for every primitive almost simple sporadic group G, with the exception of two cases involving the Baby Monster group. As a corollary, we deduce that b(G) 7, with equality if and only if G is the Mathieu group M 24 in its natural action on 24 points. This settles a conjecture of Cameron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
167
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(169 citation statements)
references
References 27 publications
2
167
0
Order By: Relevance
“…For example, suppose that H 0 = 2 G 2 (q 0 ), where q 0 = 3 l and l is odd (note that l 5 since we may assume that q 0 248). Now, if l = 5 then the hypothesis |H| q 32 implies that q 9, and applying [38, Proposition 1.3] we calculate that i 2 (H) < 2(q 0 + 1)q 3 0 < q 11 . Similarly, if l < 5 then i 2 (H) < 3 13 and the desired conclusion quickly follows.…”
Section: Proof It Suffices To Show That There Exists a Functionmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, suppose that H 0 = 2 G 2 (q 0 ), where q 0 = 3 l and l is odd (note that l 5 since we may assume that q 0 248). Now, if l = 5 then the hypothesis |H| q 32 implies that q 9, and applying [38, Proposition 1.3] we calculate that i 2 (H) < 2(q 0 + 1)q 3 0 < q 11 . Similarly, if l < 5 then i 2 (H) < 3 13 and the desired conclusion quickly follows.…”
Section: Proof It Suffices To Show That There Exists a Functionmentioning
confidence: 91%
“…However, this is strictly an existence result and the proof of [48, Theorem 1.3] does not yield an explicit value for c. Recently, a number of papers have appeared where more explicit base size results are obtained. For example, in the forthcoming paper by T. C. Burness, R. M. Guralnick and J. Saxl, 'Base sizes for actions of simple groups', it is shown that if G has socle A n and n > 12 then b(G) = 2 for all non-standard actions; it quickly follows that b(G) 3 for all n. Minimal base sizes for standard actions of alternating and symmetric groups are determined by James in [29], while precise results for primitive actions of sporadic groups will appear in the forthcoming paper [11]. Non-standard actions of finite classical groups are considered in [7] where it is shown that either b(G) 4, or G = U 6 (2).2, G ω = U 4 (3).2 2 and b(G) = 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, if b(G) = 2, then H has a regular orbit on Ω, so G is not extremely primitive. In [5,6] (see also [10,15]), the primitive almost simple groups G with b(G) = 2 and socle a sporadic or alternating group are determined. This observation greatly simplifies the proof of Theorem 1.1 since we can immediately eliminate the cases with b(G) = 2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the main theorem of Burness, O'Brien and Wilson [6] on base sizes, in our analysis of sporadic groups we make use of the data recorded in the Web Atlas [17] on permutation representations and maximal subgroups of sporadic groups. In many cases, this information allows us to construct G and H as suitable permutation groups (using GAP [9] or Magma [1]) and then quickly determine whether or not G is extremely primitive.…”
Section: Introductionmentioning
confidence: 99%